Peran Minat Beli dalam Memediasi Pengaruh Harga dan Kualitas Produk Terhadap Keputusan Pembelian pada Angkringan Hitam Putih - Handayani; Bayu Kurniawan; Aditiya Pratama Nugroho (Universitas PGRI Semarang, 2026)
This study aims to analyze the effect of Price and Product Quality on Purchase Decision at Angkringan Hitam Putih with Purchase Intention as a mediating variable. This study employs a quantitative approach with a causal design to examine both direct and indirect relationships among variables. Data were collected through a questionnaire using purposive sampling method, targeting consumers aged above 17 years who had made a purchase at Angkringan Hitam Putih. The total sample consisted of 160 respondents. Data analysis was conducted using Structural Equation Modeling (SEM) with the assistance of AMOS software. The results indicate that Price and Product Quality have a positive and significant effect on Purchase Intention, but do not have a significant effect on Purchase Decision. Purchase Intention also does not significantly affect Purchase Decision, thus failing to mediate the relationship between Price and Product Quality toward Purchase Decision. These findings suggest that consumers' perceptions of Price and Product Quality are capable of shaping Purchase Intention, but are not sufficient to drive Purchase Decision either directly or through mediation.